Extended Nonsingular Terminal Sliding Surface for Second-Order Nonlinear Systems - Ji Wung Jeong; Ho Suk Yeon; Kang-Bak Park (Abstract and Applied Analysis)
An extended nonsingular terminal sliding surface is proposed for second-order nonlinear systems. It is shown that the proposed surface is a superset of a conventional nonsingular terminal sliding surface which guarantees that the system state gets to zero in finite time. The conventional nonsingular sliding surfaces have been designed using a power function whose exponent is a rational number with positive odd numerator and denominator. The proposed nonsingular terminal sliding surface overcomes the restriction on the exponent of a power function; that is, the exponent can be a positive real number. Simulation results are provided to show the validity of the main result.